Some Noncontractive Maps on Incomplete Metric Spaces Have Also Fixed Points. (6th August 2019) - Rashid, Tawseef; Khan, Qamrul Haq; Mlaiki, Nabil; Aydi, Hassen
Abstract : In this article, we discuss a new version of metric fixed point theory. The application of this newly introduced concept is to find some fixed point results where many well-known results in literature cannot be applied. We give some examples to illustrate the given concepts and obtained results.